O Espírito sopra onde quer: Renovação Carismática Católica em Cáceres – MT - Cuyabano, Felippe Otávio de Souza (2018)
The present research investigated an activity of the Catholic Charismatic Renewal (CCR) in the religious field of the city of Cáceres, located in the State of Mato Grosso. In this context, this research carried out an ethnographic study on the thesis that the local experience of the CCR formulated a profile of Catholicism-charismatic diverse from the national identification of the Renovation, by producing new social agents in the form of leaders from the periphery , previously restricted to the traditional Catholicism, and the margin of the hierarchy of the Roman Catholic Church (IC), but which, in turn, due to such specificity in the renewed Cacerian segment, generated social contexts that allowed the transfer of these leaderships to the political field, provoking new tensions between such power spaces. In the perceptual chain of the CCR, there are different sources of origin than the scholars of the religious phenomenon, such as Prandi (1998), Carranza (2000), Souza (2005) and Sofiati (2011) is strongly marked and originating in the middle and higher economic social strata. Through a framework, the following questions stand out: Is the CCR assuming popular dimensions through social media outlets? In the local internal negotiations of the sub-field of charismatic Catholicism, can it be said that the CCR is not only filling up, but spreading, from the space of popular Catholicism in the peripheries? Different from the case of the CCR addressing the impoverished, as in its popularization on 1990s, today, would it be the impoverished ones who would speak for the RCC? In order to answer these questions for the trajectory, an ethnographic course with theoretical and methodological support, counting, among other scholars of the religious phenomenon, as reflections of Max Weber, Pierre Bourdieu, in his concepts of social action, habitus and religious field structure, which inspire the Analysis of data collected in the ethnographic trajectory, bibliographical publications, in-person incursions into the fieldwork in ministry service meetings, prayer meetings, diocesan congresses, spiritual formations, vigils, charismatic Catholic-shows, healing and liberation camps, in order to consider, the CCR faithful as research subjects for the consolidation of empirical data